Proposed new interior design of Mitsubishi Showroom (3s) for Mitsubishi Malaysia Sdn Bhd at Lot 24, Jalan Juruhebah U1/50, Temasya Industrial Park Phase 2, Seksyen U1, Glenmarie, Shah Alam / Greg Nickdle Florian - Florian, Greg Nickdle (Faculty of Architecture, Planning and Surveying, 2010)
A final year student of Interior Design is required to prepare a final year project. All the design must be related to the project that have been choose. Before doing the design, main aspect must be considered to get the information. So that, we must do a research, case study, design schematic and the planning to make sure that client will give the good feedback with our design. Proposed new interior design of Mitsubishi Showroom (3s) is a one of the direct advantages to Mitsubishi Malaysia Sdn Bhd. It is because, followed the objective and the issues and a space planning was come out with the design concept and the images. So, to implement the design into the space is a complicated way because it has the stages we must follow. The planning that we have been created and the ideas that we want to implement into the space must be related to the concept and the images. With the concept ‘Extraordinary’ and modern image will implement into the space. So, conclusion is, the good design is how we implement the concept and the images into the design cafe, followed by the development of ideas.